The first DK Tank International Conference on obstetrics, gynecology and fertility. (January 2011) - Stoop, Dominic; Devroey, Paul
The DK Tank Memorial Conference was held on 17–19 September 2010 at the Renaissance Hotel and Convention Center (Mumbai, India). The conference was hosted by the Mumbai Obstetrics and Gynecological Society (MOGS), the Federation of Obstetrics and Gynecological Societies of India (FOGSI), the South Asian Federation of Obstetrics and Gynecology (SAFOG), the Asia–Oceania Federation of Obstetrics and Gynecology (AOFOG), and the DK Tank Foundation. The conference was held in the memory of Dr DK Tank, an eminent obstetrician and gynecologist, and a prominent figure on the national and international academic scene. He was a past president of a number of local, national and international professional organizations such as the MOGS, FOGSI, SAFOG and AOFOG.